PEMBINAAN ORANG TUA DALAM MENCEGAH PENYALAHGUNAAN NARKOBA BAGI REMAJA - Erida Eri; Zuwirda Ida (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2020)
ABSTRACT Many adolescents are involved in drug abuse, this is marked by the rise of apprehension by officers against adolescents who commit drug abuse, even this is also supported by data (Kanwil Menkumham Sumbar 2020) which states that at the nowadays, the Association of Suppliers and Institutions is inhabited by most by teens and two-thirds is caused by drug abuse. This condition, if left unchecked, will certainly be worrying because adolescents are the hope of a nation that will later become leaders. To overcome this problem, it is certainly not enough to be left to the authorities, government agencies, community leaders starting from the village level to the central level. Certainly not less important is the parents because parents are the first school for children. Therefore, on this occasion the author will focus this study on how the coaching is done by parents of adolescents in preventing drug abuse. This study is a field research using a qualitative method with a descriptive approach. Data collection was carried out using the method of observation and interviews relating to coaching parents in preventing drug abuse for adolescents. The subjects in this study were parents of adolescents involved in drug abuse, and were determined by purposive sampling technique. The results of this study reveal that: Parental guidance in preventing drug abuse for adolescents is exemplary by parents who have never been involved in drug abuse. Habits of parents by always inviting their children to pray, read the Koran, and forbid teenagers not to wander the night. Advice given by parents by advising children not to get involved in drug abuse. Attention and supervision by parents to find out what their children do when outside the home. Punishment is done by parents for not giving their children spending money, and even with a slap